Improving Scientific Literacy of Elementary School Students through Problem-Based Learning Model with Balinese Local Wisdom - Ni Luh Dina Restiani; I Gede Margunayasa; Made Vina Arie Paramita (Universitas Pendidikan Ganesha, 2023)
Students' scientific literacy in elementary school is currently low. This is due to the implementation of the learning process that was not in accordance with the purpose of science learning and the implementation of learning still tends to be teacher-centered. Students have not been able to use their science knowledge to solve the problems that related to daily life. The purpose of this research was to analyze the effect of problem-based learning model with Balinese local wisdom on students' scientific literacy. The type of this research was quasi-experimental research. The population of this research were fifth grade of elementary school students. The research sample was selected by using random sampling with a total sample size of 55 students. Data were collected by test method. The instrument that used to collect data was scientific literacy test. The steps of data analysis were data description, prerequisite analysis test, and hypothesis testing. The study result showed significant differences in students' scientific literacy between groups of students who were taught with problem-based learning model with Balinese local wisdom and conventional learning model. Scientific literacy in students who learn with problem-based learning model with Balinese local wisdom are higher than students who learn with conventional learning model. This research implies that problem-based learning model with Balinese local wisdom can be used by teacher in learning to improve scientific literacy in students.